Marginal zone lymphomas with monocytoid morphology express T-bet and are associated with a low number of T cells in extranodal locations. Issue 1 (January 2014) - Lohneis, Philipp; Wienert, Stephan; Klauschen, Frederick; Ullrich, Andrea; Anagnostopoulos, Ioannis; Jöhrens, Korinna
Abstract The presence of tumor cells with monocytoid morphology in marginal zone lymphoma (MZL) has been described previously. Reactive monocytoid B cells bear a distinct immunophenotype and typically express T-bet, which clearly distinguishes them from nodal marginal zone B cells. The latter are positive for CD27 and negative for T-bet. We analyzed 74 MZLs for the expression of T-bet and correlated these results with the presence of monocytoid morphology. Expression of T-bet correlated with the presence of monocytoid morphology in MZLs. In analogy to reactive monocytoid B lymphocytes, we also found a significantly lower relative amount of intratumoral T lymphocytes in extranodal MZL with monocytoid morphology.